2017
DOI: 10.1371/journal.pone.0178865
|View full text |Cite
|
Sign up to set email alerts
|

Specific gene expression signatures induced by the multiple oncogenic alterations that occur within the PTEN/PI3K/AKT pathway in lung cancer

Abstract: Hyperactivation of the phosphatydil-inositol-3' phosphate kinase (PI3K)/AKT pathway is observed in most NSCLCs, promoting proliferation, migration, invasion and resistance to therapy. AKT can be activated through several mechanisms that include loss of the negative regulator PTEN, activating mutations of the catalytic subunit of PI3K (PIK3CA) and/or mutations of AKT1 itself. However, number and identity of downstream targets of activated PI3K/AKT pathway are poorly defined. To identify the genes that are targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 89 publications
(80 reference statements)
2
47
0
Order By: Relevance
“…The HCC in vitro studies suggested that overexpression of ST6GAL1 in HCC cells increased activation of the PI3K/Akt signalling pathway (42). Hyper-activation of the PI3K signalling cascade is well documented in several different cancer subtypes as regulating and promoting hyper-proliferation of oncogenic cells (47)(48)(49)(50). If ST6GAL1 can activate PI3K/Akt signalling, as suggested by Zhao et al (42) this may point towards mechanistic link between ST6GAL1 upregulation and increased cellular proliferation.…”
Section: St6gal1 In the Hallmarks Of Cancermentioning
confidence: 89%
“…The HCC in vitro studies suggested that overexpression of ST6GAL1 in HCC cells increased activation of the PI3K/Akt signalling pathway (42). Hyper-activation of the PI3K signalling cascade is well documented in several different cancer subtypes as regulating and promoting hyper-proliferation of oncogenic cells (47)(48)(49)(50). If ST6GAL1 can activate PI3K/Akt signalling, as suggested by Zhao et al (42) this may point towards mechanistic link between ST6GAL1 upregulation and increased cellular proliferation.…”
Section: St6gal1 In the Hallmarks Of Cancermentioning
confidence: 89%
“…A number of studies showed that PI3K/AKT was involved in human lung cancer [30-33]. Previous studies identified activation of the PI3K/AKT pathway and observed it in human lung carcinomas [34, 35]. Another study showed that PI3K/Akt regulated the expression of angiogenic factors in A549 lung cancer cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-AKT pathway in cancer has been shown to inhibit apoptosis (Zilberman et al, 2009 ). In previous studies, it has been proposed that AKT1(E17K) mutations induce proprioceptive activation by localizing to the stromal membrane in a PI3K-independent manner (Brugge et al, 2007 ; Do et al, 2008 ), promote regeneration and activation of the cell membrane (Furukawa et al, 2005 ; Shi and Hruban, 2012 ; Garcia-Carracedo et al, 2013 ), and stimulate PI3K-AKT signaling, resulting in uncontrolled cell proliferation, increased cell survival, and accelerated cellular invasion (Keniry and Parsons, 2008 ; Guo et al, 2010 ; Lauring et al, 2010 ; Mancini et al, 2016 ; De Marco et al, 2017 ). It was shown that the E17K mutation not only promotes membrane localization, but that in the absence of serum the mutant cells exhibit enhanced phosphorylation of serine 473 (Ser473) and threonine 308 (Thr308) [a conformational change after AKT-forming plasma membrane targeting that exposes two key amino acids (Vivanco and Sawyers, 2002 ; Landgraf et al, 2008 )], resulting in constitutive activation of Akt1 (Askham et al, 2010 ).…”
Section: Pi3k-akt/pkb Signaling Pathway and Akt1(e17k) Mutationmentioning
confidence: 99%
“…The AKT1(E17K) mutation promotes migration and invasion of human lung epithelial cells, enhancing their oncogenic and metastatic potential (De Marco et al, 2015 ). The formed tumors are able to spread in mice and colonize the lungs (Do et al, 2010 ; De Marco et al, 2017 ).…”
Section: The Effects Of Akt E17k Mutation Across Various Tumorsmentioning
confidence: 99%